Determination of the efficiency of different adsorbent materials (Bagasse pith, rice hulls, Paper, Clay, Sawdust) in reducing the toxicity of the wastewater from chemistry laboratories in UPV Miag-ao. - Teran, Mark P (2010.)
The chemistry laboratories in UPV Miag-ao produced a lot of wastewater. Majority of these wastes are usually not treated and are kept in a storage house and are later thrown away. This study aims to reduce the toxicity of these wastewaters using locally available and cheap adsorbent materials such as bagasse pith, rice hulls, paper, clay and saw dust. The pwedered/grounded adsorbents were loosely packed into a column and were soaked in the wastewater in different volume ratios and different lengths of time. The most efficient adsorbents and the most efficient set-up were determined by calculating the average percent mortality. The treated wastewater samples were introduced to 1 day old brine shrimps (Artemia salina) in different concentration following the produce of the Whole Effluent Toxicity (WET) testing. Significant differences among the mortality of each other adsorbent materials were determined using One-way ANOVA and Tukeys HSD Post Hoc test as statistical analysis. Results for the WET test showed that the most efficient adsorbent was sawdust followed by clay. These two adsorbents have been mixed with charcoal to obtain better results. Qualitative characterization of the wastewater samples were aslo done and includes the determination of physical appearance, water reactivity, water solubility, ignitability, pH and the presence of halogens.
Thesis (Undergraduate, Bachelor of Science in Chemistry) College of Arts and Sciences, University of the Philippines Visayas, Miagao, Iloilo.
Keywords: Adsorbent Materials